ChemInform Abstract: Cascade‐ and Orthoamide‐Type Overman Rearrangements of Allylic Vicinal Diols. Issue 4 (28th January 2014) - Nakayama, Yasuaki; Sekiya, Ruriko; Oishi, Hiroki; Hama, Naoto; Yamazaki, Miki; Sato, Takaaki; Chida, Noritaka
Abstract Two novel types of Overman rearrangements from vicinal diols are developed by simply changing the reaction conditions.